1988
DOI: 10.1016/0014-5793(88)80991-8
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering changes and protein distortion in the bacteriorhodopsin during the photocycle

Abstract: A change in light scattering was detected during the photoeycle of the purple membrane. A systematic study of the pH, viscosity and photoseleetion dependence of scattering kinetics is given. From the experimental data it follows that purple membranes are bent, depending on the pH, and that the extent of bending changes during the photocycle is due to the functional protein. A theoretical treatment is also given. The model explains all the experimental data and, as an important consequence, calls attention to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…According to the structure data of the intermediates the motions in PRG seem to be small. However, large bending of pm associated with the photocycle was found by two methods: light scattering (11)(12)(13) and electrooptics (14). The time-resolved light scattering data show that the bending appears already during M formation (11)(12)(13), whereas the published electrooptical measurements that deal with pm containing the mutant BR D96N assign it in general to the M intermediate resolving only its decay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the structure data of the intermediates the motions in PRG seem to be small. However, large bending of pm associated with the photocycle was found by two methods: light scattering (11)(12)(13) and electrooptics (14). The time-resolved light scattering data show that the bending appears already during M formation (11)(12)(13), whereas the published electrooptical measurements that deal with pm containing the mutant BR D96N assign it in general to the M intermediate resolving only its decay.…”
Section: Discussionmentioning
confidence: 99%
“…However, large bending of pm associated with the photocycle was found by two methods: light scattering (11)(12)(13) and electrooptics (14). The time-resolved light scattering data show that the bending appears already during M formation (11)(12)(13), whereas the published electrooptical measurements that deal with pm containing the mutant BR D96N assign it in general to the M intermediate resolving only its decay. Careful analysis of light scattering data (11)(12)(13) indicates that the pm at pH.5 (as in our case) bends toward the extracellular side suggesting that PRGs in triplet come somewhat nearer to each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a possible origin of such a decrease, transient changes in the curvature of the membranes could be considered. However, light-scattering experiments have shown that in the gel the membrane is unable to change its curvature (i.e., bending processes associated with the bR photocycle in solution are absent ). The possibility of significant transient changes of S 2 in our experiments is thus excluded.…”
Section: Discussionmentioning
confidence: 99%